Calidad De Vida Y Niveles De Actividad Física En Estudiantes De La Facultad De Ciencias De La Educación - Tapia Valle, Cristian Andres (2019)
This research project to the quality of life and physical activity levels in the first semester students at the of educational sciences faculty of the National University of Chimborazo it has as main objective, determine the quality of life and its physical activity levels. The population with which we worked was 1750 male and female university students from where the intentional sample we used was 296 students all attending the first semesters of the different careers of the Educational Sciences Faculty with an intentional sample containing 184 female students and 112 male students who are within the ages of 18 to 25 years old, this research was based on an analytical – descriptive research type with a cross-section and qualitative – quantitative nature. The survey was used as a research technique with an instrument called University Students Displacement Questionnaire Quality of life and physical condition where according to the data tabulation we obtained as a result that students have an acceptable quality of life and physical condition.